Description Of Capabilities Of Ners Students Stageacademic Conduct Self Directed Learning During The Covid 19 Pandemic At Stikes Santa Elisabeth Medan, 2022 - Rotua Elvina Pakpahan; Ance M. Siallagan; Deslima Simanjuntak (Sean Institute, 2023)
The Covid 19 pandemic has had an impact on the learning system, namely that there has been a change in learning technology, from what was usually carrying out face-to-face learning drastically now changing to online or online-based learning without face-to-face meetings. This study aims to describe the ability of students to do self-directed learning at STIKes Santa Elisabeth Medan. This type of research uses a descriptive design with a sample of 389 people. The results of the study show an overview of the ability of graduate students at the academic stage to do self-directed learning with high (69.2%) and moderate (30.8%) abilities. students are aware of and apply various learning strategies, learning awareness, learning activities, evaluation, and interpersonal skills during the covid 19 pandemic, From the results of this study it is hoped that the STIKes Santa Elisabeth Medan educational institution can maintain and increase student learning independence, even though the Covid 19 pandemic is over, students are still implementing self-directed learning.